STUDI DESKRIPTIF KOMPETENSI PEDAGOGIK GURU MEMBUAT PENILAIAN AFEKTIF PADA PEMBELAJARAN PPKN di KELAS V SDN 02 KOTA BENGKULU - Cintia Fraditha Setia Diningrum Setia Diningrum; Puspa Juwita; Osa Juarsa (Jurnal Kajian Pendidikan Dasar (Kapedas), 2022)
The general objectives of this study are: To describe the pedagogical competence of teachers in making affective assessments of PKN learning in class V SDN 02 Bengkulu City. The specific objectives of this study are: 1. To describe the competence of teachers in making a grid of affective assessment instruments in accordance with PKN learning. 2. To describe the performance of teachers formulating affective assessment rubrics in PKN learning. 3. To describe the obstacles experienced by teachers in making assessments of the affective domain and their solutions. 4. To describe the implementation of affective assessment in PKN learning. Judging from the type of data, the research approach used in this study is a qualitative approach. This study uses a qualitative descriptive research method. In this study, the subject of the study was the teacher of class V 02 Bengkulu City consisting of class Vb which amounted to one person. Data collection techniques used in this study were observation, interviews, and documentation.